The Theme of Laborers in Contemporary Chinese Painting: A Study of Historical Mission and Artistic Expression - Xing, Lu; Haslinda Abd Razak,; MOHAMMAD NOH, LIZA MARZIANA (Advances in Humanities and Contemporary Studies, 2023)
Since the founding of New China, the image of laborers has always been one of the important themes in Chinese painting creation. It is an artistic expression of Chinese political thought and the life of the Chinese people. Shaping and praising laborers has become an important historical mission of contemporary Chinese artists.This study aims to examine the differences between laborer images in modern and contemporary Chinese paintings by analyzing works from the 7th National Youth Art Exhibition and the 13th National Art Exhibition.The study draws three conclusions: In terms of subject matter, the new labor and production relations have updated and enriched the connotation of Chinese contemporary figure painting; In terms of narrative features, it is manifested in the transformation from the grand narrative to the individual narrative; From creation, The technique is manifested as multiple aesthetic orientations based on realism.The ultimate purpose of the article is to try to show that Chinese painting with the theme of labor is an integral part of contemporary Chinese painting, reflecting the development, success, and confusion of contemporary Chinese painting in the evolution of the times. Most importantly, it records and reflects the times in an artistic way on the surface, but in essence, illuminates social life with a humanistic spirit.